Effects of cottonseed flour on immunohistochemical localization of androgen receptors (AR) in rat testes - Timurkaan, N.; Yilmaz, F.; Timurkaan, S. (Ecole Nationale Veterinaire Toulouse, 2011)
The objective of the present study was to investigate the effect of the consumption of the gossypol rich cottonseed flour (CSF) on immunohistochemical localization of androgen receptors (AR) in rat testes. For that. 50 male rats were divided into 5 equal groups according to the CSF content (0%. 5%. 10%. 20% and 40%) added to the standard ration for 20 and 60 days. The corresponding gossypol doses measured by spectrophotometry were 0.641. 1.282. 2.654 and 5.128 g/kg of food respectively. The AR localization in Leydig. Sertoli and peritubular myoid cells was determined by semi-quantitative immunohistochemistry after fixation of testes in 10% neutral buffered formalin and staining with the streptavidin-biotin-peroxidase method. All dietary CSF treatments significantly decreased the AR nuclear expression in the 3 cell types except for 5% CSF in the Leydig cells. These effects were dose and time dependent and the variations coefficients varied from -1.8% to -84.9% in the Leydig cells, from -22.5% to -99.3% in the Sertoli cells and from -35.5% to -88.9% in the myoid cells. These results clearly demonstrated the adverse effects of the CSF and gossypol on the AR expression in rat testes. particularly in the Leydig and Sertoli cells which can lead to infertility.
Keywords: Cottonseed flour; rat; androgen receptor; immunohistochemistry; testes; Leydig cells; Sertoli cells; Myoid cells